Mudança na paisagem no Assentamento Chidaua - Zambonin, Roseli Vieira (2014)
The implementation of projects of rural settlements and the opening of roads in the Amazon region are major villains of deforestation, which has been accelerated, uncontrolled and unplanned manner, thus causing a high increase in environmental problems and changes in the landscape. This research aimed to understand the evolution of the landscape in rural Chidaua Settlement, in the municipality of Caracaraí - Roraima, from the perspective of landscape ecology. This settlement was created from the dismemberment of PAD Anauá in 2006, with a capacity to seat 158 families. The work was organized in three chapters. The first chapter is titled as changes in the landscape caused by the occupation process, aimed to detect changes in the landscape resulting from human action. The results were obtained by processing a series of remote sensing images for the years 1984, 2000 and 2011 which were analyzed and processed in the computer lab of the Graduate Program in Geography UFRR. The results showed a high growth rate of deforestation, from 496.74 km ² of dense forest in 1984 to 341.2 km ² in 2011, a decrease of 155.54 km ² of forested areas. In the second chapter are the social, environmental and cultural aspects of farmers who actually reside in the study area. The results were obtained from the application of 40 questionnaires, on-site visit and photographic record. These procedures allowed us to know the environmental reality of resettled farmers and concluded that the process of deforestation in this area is justified by the existence of various problems that influence the farmer to continue the cycle of deforestation, some of which are: the establishment of settlements in poor lands and inadequate, lack of infrastructure, an efficient technical assistance and also for public policy that ensures the economic sustainability of these settlers. And finally in the third chapter, some suggestions for sustainable activities to improve the quality of life of farmers were presented.